Service features and interest in transactions regarding the use of fund applications for employees at the El Fajr Qur'an home education foundation, Palembang city - Setiawan, Bagus; Ria Astina; Cindi Pramita (Jurnal Ekonomi, 2024)
With the development of increasingly advanced technology in the world, every small and large company is competing to develop their system, one of which is a service system that is easy and practical. The aim of this research is to understand service features regarding transaction interest in using digital fund applications. The method used in this research is a qualitative method to describe or explain current phenomena that have passed. This method aims to provide a description, explanation and validation of the results of the role of digital service features in attracting interest in transactions using fund applications, especially for employees in El Fajr Qur'an House Education Foundation, Palembang City.